Hands-Free Conventional Radiographic Ventrodorsal Hip Extended View - Santana, Ana; Alves-Pimenta, Sofia; Martins, João; Colaço, Bruno; Ginja, Mário (Frontiers in Veterinary Science, 2020)
Hip dysplasia (HD) is an important hereditary orthopaedic disease in the dog associated with osteoarthritis and inadequate welfare for affected animals. The radiographic ventrodorsal hip extended (VDHE) view is used worldwide to select the better animals for breeding. This view normally is performed with manual restraining of the dog to obtain radiographs with acceptable technical quality. The veterinarian exposition to ionizing radiation is inevitable. In this study was compared the technical quality of VDHE radiographs and hip measurements in 65 dogs radiographed twice, one with the common veterinarian manual restraining and other was obtained using a hind limb holder device, without the veterinarian within the X-ray room. The variables studied were pelvic tilting, patella displacement index, Norberg angle (NA) and subluxation hip category. The results showed a random distribution of right and left pelvic tilting, patella lateral or medial displacement and hip subluxation categories in both samples (P>0.05). The holder device positioning showed a better pelvic symmetry (P<0.05) and a similar patellar displacement (P>0.05). The mean ± standard deviation of NA was 101.1±6.2º and 100.9±6.1º in the manual and holder device hind limb restraining, respectively (P>0.05) and the lower limit of 95% confidence interval of intraclass correlation coefficient was > 0.75. These results showed statistical reproducibility of NA measurements by the hind limb holder device and the examiner is protect of exposure to ionizing radiation within x-ray room.